Inspection of a novel penetration enhancer for transungual drug delivery system: Pelargonium hortorum - Singh, Vikram; Chandrul, Kaushal Kishore (Journal of Applied Pharmaceutical Research, 2015)
This study was to search some natural penetration enhancer and formulate them inÃÂ  a transungual drug delivery formulation. This natural penetration enhancer helps to overcome the main problem in front of success of transungual drug delivery system. We selected to formulate fluconazole as a model drugÃÂ  for the nail fungal infection treatment with extracted penetration enhancer (PE). Model drug i.e. fluconazole was formulated with the natural extracted penetration enhancer with different deigned formula. The solvent for PE extraction was methanol and that extracts were air dried.ÃÂ